Pengeringan Kerupuk Kemplang Menggunakan Alat Efek Rumah Kaca Di Desa Jejawi Kabupaten Ogan Komering Ilir (OKI) - Muhrinsyah Fatimura; Muhammad Bakrie; Rully Masriatini; Reno Fitriyanti; Husnah; Aan Sefentry; Nurlela; Agus Wahyudi (Unika Santu Paulus Ruteng, 2023)
Kemplang crackers are a traditional food that is very popular with Indonesian people. In the process of making it, it requires proper drying process so that when frying it produces crispy kemplang crackers when eaten. The problem in society is that the drying process is not optimal due to weather factors resulting in a reduced production process or product quality not as desired. For this reason, the Chemical Engineering Study Program held PKM in Jejawi village. By designing a kemplang cracker dryer by utilizing the greenhouse effect it is designed to overcome the existing problems. From the results of direct testing in the field in Jejawi village, the water content can be separated up to 6.95%.